The interactive communication context: factors influencing communication between nurses and hospitalised children - Ana Lucía Noreña Peña; Luis Cibanal Juan (Cultura de los Cuidados, 2012)
Introduction. Communication comprehends an interaction, and often is a synonym of relationship, which gives the connotation of affinity between the people that participate in it. In the case of hospitalized school children 8-14 years old, the interactive communication with adults plays a fundamental role, since it is this one that provides the understanding of the experience of disease and the adaptation to the hospital stay. Objective. To understand the dynamics of the hospital environment (pediatrics service), as well as the communication process between the hospitalized child and the nurse. The study describes the aspects involved in this interaction, and what the child builds around what it is communicated to him/her. Methodology. This is a descriptive–exploratory research, based on the qualitative methods of data collection and analysis. The data collection for this research was done with participating observation techniques and deep interviews with semi-structured questions. Conclusions. Amongst the principles of communication within the health system, the challenge must be to create a cooperative way of communication to make sense for both (professional- child/family). If more efforts to obtain these data were made, the health care could be adapted to the real child’s needs.